FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN SEKSUAL PADA IBU HAMIL - Meilani, Niken; Setiyawati, Nanik (Poltekkes Kemenkes Yogyakarta, 2015)
Pregnancy was a time of physical and psychological change in conjunction with cultural, social, emotional influence. There is a change in of-sexual function during pregnancy. The studies concerning sexuality in pregnancy were limited. This study aims to determine sexual satisfaction among pregnant women, such as characteristics (age, education level, job status, parity), pregnancy period, frequency of intercourse and initiatives of intercourse. This type of research is correlational analytic studies using cross-sectional survey. This study is the place of each District/ City of randomly selected health centers. five Public health centers were selected.The subjects of this study were pregnant women who visited the health center from August to October 2014, the amount of 99 people. The results of this study showed there is a correlation between pregnancy period and sexual satisfaction (p value= 0.01). No correlation between frequency of intercourse (p-value = 0.195), and initiative of intercourse (p-value =0.231 )  andsexual satisfaction during pregnancy.